Sustainable banking: the greening of finance (Sheffield, 2001)
"Through the use of case studies and detailed analysis, this book examines the environmental policies of banks, the importance of transparency and communication with their stakeholders, environmental and ethical investment funds, current practice by the providers of financial services with regard to environmental risk management and, finally, the key role of government, NGOs and multilateral banks in delivering sustainability."